Strategi Peningkatan Kesejahteraan Petani Melalui Diversifikasi Hasil Pertanian - Andriyanto (CV. SINAR HOWUHOWU, 2025)
The welfare of farmers remains a central issue in Indonesia’s agricultural development. This study aims to examine diversification of agricultural products as a strategic approach to enhance farmers' economic resilience and improve their livelihoods. Using a qualitative case study method, data were collected through interviews, field observations, and focus group discussions in two agricultural regions: Kulon Progo and Karanganyar. The results show that most farmers have implemented horizontal and vertical diversification, including the cultivation of various horticultural crops and the processing of raw products into higher-value goods. This diversification has led to increased income, the creation of rural employment opportunities, and strengthened community resilience. However, challenges such as limited access to capital, market constraints, and inadequate institutional support persist. The study concludes that effective diversification requires integrated support from local institutions, government policies, and community-based initiatives to ensure sustainable agricultural development and farmer welfare.